1990-ЖЫЛЛАР ҚАРАҚАЛПАҚ ӘДЕБИЙ СЫНЫНДА ПРОЗА МӘСЕЛЕЛЕРИ - Алланазарова, З.Ж. (ILIM hám JÁMIYET, 2026)
Special attention is being paid to the issues of prose in Karakalpak literary criticism. In the article related to the scope of the work, literary and critical materials published in the 1990–2000s in the “Amudarya” journal, as well as in the newspapers “Erkin Karakalpakstan”, “Karakalpakstan jaslari”, and “Ustaz Jolı” of the Republic of Karakalpakstan, have been collected.